2007
DOI: 10.1089/jir.2006.0158
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) Is a Potent Rat Mast Cell Chemoattractant

Abstract: It is well known that mast cell number increases in local tissues under different pathophysiologic conditions, although the humoral factors that stimulate local mast cell accumulation within tissues are not yet well known. Taking into account that tumor necrosis factor (TNF) influences tissue mast cell activity in various ways, the aim of the present study was to investigate the chemotactic activity of TNF for rat peritoneal mast cells. We have found that TNF induces mast cell migratory response in a dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…These observations implicate that the increased tryptase in the airway tracts of COPD patients or CS rats is likely originated from mast cells situated in bronchial tissues, rather than in the cavity of airway tracts. Smoking-induced accumulation of mast cells in bronchial tissues has been found previously (Ekberg-Jansson et al 2005), which is mediated by histamine (Godot et al 2007) or TNF (Brzezińska-Błaszczyk et al 2007) related mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…These observations implicate that the increased tryptase in the airway tracts of COPD patients or CS rats is likely originated from mast cells situated in bronchial tissues, rather than in the cavity of airway tracts. Smoking-induced accumulation of mast cells in bronchial tissues has been found previously (Ekberg-Jansson et al 2005), which is mediated by histamine (Godot et al 2007) or TNF (Brzezińska-Błaszczyk et al 2007) related mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…We did found that dihydrotestosterone treatment increased the mRNA of 2 purported TWIST11-responsive genes, CCL2 and TNF-a. TNF-a is also a potent chemoattractant for several cell lines (49). However, the effect of androgen on CCL2 and TNF-a mRNA appeared to be AR-dependent pathway but not TWIST1-dependent.…”
Section: Discussionmentioning
confidence: 94%
“…Stimulate migration of MC [107] ; promote cellular differentiation, survival, and production of inflammatory cytokines and chemokines [156] .…”
Section: Indution Of Eos and Neu Accumulationmentioning
confidence: 99%
“…For example, the interactions of eotaxin, RANTES and MCP-1 with CCR3 (CD193) are responsible for the recruitment of basophils, eosinophils and mast cells [104] . While IL-6 [105] , IL-8 [106] , and TNF [107] stimulate mast cells migration [108] , and IL-29 induces mast cell infiltration via CD18-and intercellular adhesion molecule-1 (ICAM-1)-dependent mechanisms [101] .…”
Section: Wwwchinapharcom He Sh Et Almentioning
confidence: 99%